The effect of lead acetate administration to the uterine malondialdehyde level and endometrial thickness in albino rats (Rattus novergicus) (Medical Journal of Indonesia, 2018)
Background: Indonesian seawater has been found to contain a high level of lead acetate and tends to become toxic. The previous study suggested lead acetate exposure could be harmful to many organs including the brain, liver, heart, as well as the reproductive system. This study aimed to analyze the effect of lead acetate on both the uterine level of malondialdehyde (MDA) level and endometrial thickness in female Wistar rats (Rattus norvegicus).Methods: Twenty-four rats were divided into 4 groups: 1 control group, and 3 treatment groups that were given lead acetate at 30, 100, and 300 ppm p.o./day for 30 days, consecutively. Rats were sacrificed; the uterus was isolated and processed for both MDA level measurements (using TBARS and a spectrophotometer) and histopathology using hematoxylin-eosin (HE) staining. Results: There was no significant difference in mean MDA level between the control and lead acetate administration groups. There was a reduction in endometrial thickness from 352.6±81.88 μm in the control group to 323.5±90.67 μm; 313.6±40.30 μm; 303.4±62.75 μm in 30, 100, and 300 ppm, respectively. Consequently, spacious uterus was observed reflects the endometrial damage, including the decrease in the size of the epithelium, columnar, stroma, and lumen in the whole part of the uterus and these differences in uterine thickening was considered statistically significant (p=0.005). Conclusion: Lead acetate could reduce the thickness of the endometrium but had no effect on the level of MDA in the uterus.